Lactobacillus acidophilus CRL 1014 e extrato aquoso de yacon na evolução do processo de carcinogênese química de cólon - Almeida, Ana Paula da Silva [UNESP] (2014)
Colorectal cancer is the third commonest type of cancer in both sexes in the world. Research suggests beneficial effects of consuming probiotics and prebiotics on colon cancer. The aim of this project was to define the phases of the development of colon cancer that are more affected by aqueous yacon extract, Lactobacillus acidophilus CRL 1014 and aqueous yacon extract + Lactobacillus acidophilus CRL 1014 ingested by rats chemically treated with 1,2 dimethylhydrazine (DMH) to induce colon cancer. Hundred male Wistar rats were randomly divided into five treatments: G1: untreated rats; G2: DMH; G3 (probiotic): DMH + L. acidophilus CRL 1014; G4 (prebiotic): DMH + aqueous yacon extract; G5 (synbiotic): DMH + L. acidophilus CRL 1014 + aqueous yacon extract. All treatments were administered orally for 8 months, L. acidophilus CRL 1014 was administered at 109 CFU/ mL in 3 mL/ kg body weight and amount of aqueous yacon extract administered was calculated in relation of its fructooligosaccharides (FOS) content using fructan assay kit (Megazyme®). Animals ingested 10% of FOS in diet. Five animals from each treatment group were sacrificed after the first DMH injection and in the third, fifth and eighth months. Tissues were subjected to macroscopic analysis, measuring polyp number, volume and thickness, aberrant crypt foci (ACF) analysis, histological tissue analysis, comet assay in peripheral blood, apoptosis index, and colon samples from the first sacrifice were assessed for K-67 and p53 by immunohistochemical procedures. G3, G4 and G5 showed DNA damage reduction. G5 and G3 groups showed higher apoptosis index and decrease of Ki-67, compared to G2 (p<0.05). p53 staining did not differ among G2, G3, G4, G5. G5 showed fewer ACF number per colon in third month and in the fifth month G3, G4 and G5 showed a reduction of ACF number per colon relative to G2 (p<0.05). In the last month, G3, G4 and G5 showed no effect on ACF number per colon relative to G2..